(untitled) (Revista da Tulha, 2015)
During the research process for the master’s “Symphonic Orchestra of Ribeirão Preto: Representations and Social Meaning” (HADDAD, 2009), located several personal files of musicians, former musicians and Ribeirao Preto corporations. With overcome access barriers, we find that much of the city’s history is with the people, inside homes, in family albums, the letters and newspaper clippings, personal documents, press, iconographic, as well as manuscripts and musical printed between other documents, many of them hitherto unexplored. This article presents the PhD project that aims raising historical sources of musical activities, since the city’s founding in 1856 until the mid-1980s, through the personal collections of collections: Aluísio da Prates Cruz (1931) , Belmácio Pousa Godinho (1892-1980), Conegundes Rangel, Edmundo Russomanno (1893-1963), Francisco de Assis Barros, Cônego Barros (1894-1942), Franklin Guedes Carneiro Filho, Gaetano Baccega, Homero de Sá Barreto (1884-1924), Ignacio Stábile (1889-1955), José Delfino Machado, José dos Reis Miranda Filho (1901-1956), José Luiz Baldo (1909-2010) and Manoel da Silva (1896 to 1963). Such archives and other documents related to the history of Ribeirão Preto music are deposited in the city’s homes and in local files (File Museum of Ribeirão Preto Café, Documentation Centre “Brazilian Musical Memory” of FFCLRP / USP, Music Department UNAERP, Historical Archive of the Symphonic Orchestra of Ribeirão Preto Public and Municipal Historical Archive of Ribeirão Preto). For this survey are considered historical and musicological aspects of its obvious cultural and social implications. The survey of all this data opens the way to understanding the musical movement as a characteristic of social meanings that music exercised, giving parameters for the study of the history of local music. Therefore, we established concepts to theoretical discussion: the set of characteristics and social circumstances that distinguish the company and the musical tradition of the city of Ribeirão Preto.